Investigating The Influence of Online Training and Material Mastery on Buddhist Pre-marriage Guiding Skills - Suryani Suryani; Partono Nyanasuryanadi; Burmansah Burmansah (Universitas Pendidikan Mandalika, 2024)
This research aims to investigate the influence of online training and material mastery partially and simultaneously on Buddhist pre-marriage guiding skills. This research used a quantitative approach with a correlational survey design. The population were 235 Buddhist pre-marriage guiding facilitators. The sampling technique was purposive sampling; 148 respondents were taken as samples, which was determined using the Yamane formula. This research used questionnaires as instruments with 120 items using Likert scale assessments, which were distributed to respondents after passing the validity and reliability test. Incoming data was tabulated in Excel and processed using SPSS 29. The techniques used to analyze the data were descriptive statistics and multiple linear regression Analysis, as well as the T-test, F test and Coefficient Determination test after the classical assumption test was carried out. This research showed that online training and material mastery had a positive and significant influence partially and simultaneously on the Buddhist pre-marriage guiding skills; this research indicates that the facilitators have good guiding skills in providing Buddhist pre-marriage guidance. This research also indicated that facilitators could follow the online training model well because they could use information technology to follow the learning process holistically and continuously. This research also indicated that the facilitators mastered the pre-marriage guidance material well because they know and understand the material, apply it, analyze it, evaluate it, and create or compile, summarize, combine, and formulate Buddhist pre-marriage guidance material.